Reconsidering John Calvin - Zachman, Randall C., 1953- (Cambridge ; New York : Cambridge University Press, 2012)
"Randall C. Zachman places Calvin in conversation with theologians such as Pascal, Kierkegaard, Ezra the Scribe, Julian of Norwich and Karl Barth, and attends to themes in Calvin's theology which are often overlooked. Zachman draws out Calvin's use of astronomy and great concern to see ourselves in comparison to the immensity of the universe, acknowledging in wonder and awe our nothingness before God. Throughout, Zachman presents a Calvin who seeks a route out of self-deception to self-knowledge, though Kierkegaard shows that it is love, and not judgment, that most deeply reveals us to ourselves. The book discusses Calvin's understanding of the election of the Jews and their relationship to God, and further reconsiders Calvin's understanding of judgment and how the call to love our neighbour is undermined by the formation of alliances"--
Machine generated contents note: Introduction; 1. The beauty and terror of the universe: John Calvin and Blaise Pascal; 2. The bond and critique of all social union: John Calvin and Soren Kierkegaard on the image of God; 3. The one elect people of God: John Calvin and Karl Barth on the Jews; 4. The restoration of Israel by Gospel and law: Calvin and Ezra the Scribe; 5. The comfort and the challenge of love: John Calvin and Soren Kierkegaard; 6. Hoping for all others, fearing for myself: John Calvin and Julian of Norwich; Conclusion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Calvin, Jean, -- 1509-1564.; RELIGION / Theology; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books